Cognitive Disorders - Foyaca Sibat, Humberto (IntechOpen, 2019)
This book contains selected peer-reviewed chapters that cover novel information on cognitive disorders and updated information on dementias written by international researchers. In this project, we discuss the effect of metabolic disorders on the development of cognitive disorders in patients with type 1 diabetes mellitus. In another chapter, the authors highlight the usability of an assistive software application developed for patients with dementia. On the other hand, an extensive review of novel information on different types of dementia is made. This chapter covers the novel aspect of dementia without ignoring its foundation. Therefore, apart from classic issues that cannot be missed in any textbook about cognitive disorders, we introduce updated information on the commonest dementias. The current situation of the prisoner population with dementia in a correctional setting is analyzed in another chapter, and specific recommendations to improve the health outcomes for prisoners are delivered. In more than one chapter, our authors wrote about a copious microtubule-associated protein (tau) as a biological fluid biomarker and tauopathies leading to cognitive disorder and cancer. Finally, the role of the hypothalamus in Alzheimer's disease is discussed. We look forward with confidence and pride to the remarkable role that this book will play for a new vision and mission.